Antidepressants for preventing postnatal depression - Molyneaux, Emma (Cochrane Database Syst Rev, 2018)
BACKGROUND: Depression is common in the postnatal period and can lead to adverse effects on the infant and wider family, in addition to the morbidity for the mother. It is not clear whether antidepressants are effective for the prevention of postnatal depression and little is known about possible adverse effects for the mother and infant, particularly during breastfeeding. This is an update of a Cochrane Review last published in 2005. OBJECTIVES: To assess the effectiveness of antidepressant medication for the prevention of postnatal depression, in comparison with any other treatment, placebo or standard care. SEARCH METHODS: We searched the Cochrane Common Mental Disorders Controlled Trials Register (CCMDCTR ‒ both Studies and References), CENTRAL (Wiley), MEDLINE (OVID), Embase (OVID), PsycINFO (OVID), on 13 February 2018. We also searched the World Health Organization (WHO) trials portal (ICTRP) and ClinicalTrials.gov on 13 February 2018 to identify any additional unpublished or ongoing studies. SELECTION CRITERIA: Randomised controlled trials (RCTs) of initiation of antidepressants (alone or in combination with another treatment), compared with any other treatment, placebo or standard care for the prevention of postnatal depression among women who were either pregnant or had given birth in the previous six weeks and were not currently depressed at baseline. DATA COLLECTION AND ANALYSIS: We used standard methodological procedures expected by Cochrane. We requested missing information from investigators wherever possible and sought data to allow intention‐to‐treat analyses. MAIN RESULTS: Two trials including a total of 81 participants fulfilled the inclusion criteria for this review. All participants in both studies had a history of postnatal depression and were not taking antidepressant medication at baseline. Both trials were conducted by the same research group. Risk of bias was low or unclear in most domains for both studies. We were unable to perform a meta‐analysis due to the small number of studies. One study compared nortriptyline with placebo and did not find any evidence that nortriptyline was effective in preventing postnatal depression. In this study, 23% (6/26) of women who took nortriptyline and 24% (6/25) of women who took placebo experienced postnatal depression (RR 0.96, 95% CI 0.36 to 2.59, very low quality evidence) in the first 17 weeks postpartum. One woman taking nortriptyline developed mania; and one side effect, constipation, was more common among women taking nortriptyline than those taking placebo. The second study compared sertraline with placebo. In this study, 7% (1/14) of women who took sertraline developed postnatal depression in the first 17 weeks postpartum compared with 50% (4/8) of women who took placebo. It is uncertain whether sertraline reduces the risk of postnatal depression (RR 0.14, 95% CI 0.02 to 1.07, very low quality evidence). One woman taking sertraline had a hypomanic episode. Two side effects (dizziness and drowsiness) were more common among women taking sertraline than women taking placebo. Conclusions are limited by the small number of studies, small sample sizes and incomplete outcome data due to study drop‐out which may have led to bias in the results. We have assessed the certainty of the evidence as very low, based on the GRADE system. No data were available on secondary outcomes of interest including child development, the mother‒infant relationship, breastfeeding, maternal daily functioning, family relationships or maternal satisfaction. AUTHORS' CONCLUSIONS: Due to the limitations of the current evidence base, such as the low statistical power of the included studies, it is not possible to draw any clear conclusions about the effectiveness of antidepressants for the prevention of postnatal depression. It is striking that no new eligible trials have been completed in the period of over a decade since the last published version of this review. Larger trials are needed which include comparisons of antidepressant drugs with other prophylactic treatments (e.g. psychological interventions), and examine adverse effects for the fetus or infant. Future reviews in this area may benefit from broadening their focus to examine the effectiveness of antidepressants for the prevention of perinatal (i.e. antenatal or postnatal) depression, which could include studies comparing antidepressant discontinuation with continuation for the prevention of relapse of depression during pregnancy and the postnatal period.